Optimalisasi Pembelajaran Akidah Akhlak dalam Menumbuhkan Karakter Peduli Lingkungan melalui Program P5 PPRA di MTsN 15 Jombang - 'Abidah, Arum Nur; Umam, Khoirul (Lembaga Yasin AlSys, 2025)
The development of environmentally conscious character is a vital aspect of education in Indonesia and is mandated to be implemented at every level of educational institutions. The Islamic Religious Education (Pendidikan Agama Islam or PAI) subject, particularly Akidah Akhlak, plays a strategic role in instilling moral and spiritual values that support environmental awareness. This study aims to explore the optimization of Akidah Akhlak instruction in fostering environmentally conscious character through the P5 PPRA program at MTsN 15 Jombang. A qualitative approach was employed using a case study design. Data collection techniques included observation, interviews, and documentation, with informants consisting of the principal, Akidah Akhlak teachers, and students. Data analysis was conducted through source triangulation to ensure the validity of findings. The results indicate that Akidah Akhlak instruction integrated with the P5 PPRA program effectively cultivates students’ environmental awareness. The program includes greening activities and recycling plastic bottles into ecobricks, providing students with hands-on experiences in applying moral values toward nature. The integration of religious values with environmental practices through contextual learning not only enhances students’ understanding of the importance of environmental stewardship but also strengthens their commitment to practicing it in daily life as part of their faith implementation. These findings affirm that an instructional approach combining spiritual dimensions with real-world actions can be an effective strategy for shaping ecologically minded student character.